Characterization of efficacy and safety of pathogen inactivated and quarantine plasma in routine use for treatment of acquired immune thrombotic thrombocytopenic purpura. Issue 5 (21st May 2018) - Herbrecht, R.; Ojeda‐Uribe, M.; Kientz, D.; Fohrer, C.; Bohbot, A.; Hinschberger, O.; Liu, K.‐L.; Remy, E.; Ernst, C.; Lin, J.‐S.; Corash, L.; Cazenave, J. P.
Abstract : Background: Auto‐immune thrombotic thrombocytopenic purpura (TTP) is a morbid multi‐organ disorder. Cardiac involvement not recognized in initial disease descriptions is a major cause of morbidity. Therapeutic plasma exchange (TPE) requires exposure to multiple plasma donors with risk of transfusion‐transmitted infection (TTI). Pathogen inactivation (PI) with amotosalen‐UVA, the INTERCEPT Blood System for Plasma (IBSP) is licensed to reduce TTI risk. Methods: An open‐label, retrospective study evaluated the efficacy of quarantine plasma (QP) and IBSP in TTP and defined treatment emergent cardiac abnormalities. Medical record review of sequential patient cohorts treated with QP and IBSP characterized efficacy by remission at 30 and 60 days (d) of treatment, time to remission, and volume (L/kg) of plasma required. Safety outcomes focused on cardiac adverse events (AE), relapse rates, and mortality. Results: Thirty‐one patients (18 IBSP and 13 QP) met study criteria for auto‐immune TTP. The proportions (%) of patients in remission at 30 d (IBSP = 61·1, QP = 46·2, P = 0·570) and 60 d (IBSP = 77·8, QP = 76·9, P = 1·00) were not different. Median days to remission were less for IBSP (15·0 vs. 24·0, P = 0·003). Relapse rates (%) 60 d after remission were not different between cohorts (IBSP = 7·1, QP = 40·0, P = 0·150). ECG abnormalities before and during TPE were frequent; however, cardiac AE and mortality were not different between treatment cohorts. Conclusions: Cardiac and a spectrum of ECG findings are common in TTP. In this study, IBSP and QP had similar therapeutic profiles for TPE.